Improved secretory expression and characterization of thermostable xylanase and β-xylosidase from Pseudothermotoga thermarum and their application in synergistic degradation of lignocellulose - Chen, Jinkang; Qin, Hao; You, Chaoqun; Long, Lingfeng (Frontiers in Bioengineering and Biotechnology, 2023)
Xylanase and β-xylosidase are the key enzymes for hemicellulose hydrolysis. To further improve hydrolysis efficacy, high temperature hydrolysis with thermostable hemicellulases showed promise. In this study, thermostable xylanase (Xyn) and β-xylosidase (XynB) genes from Pseudothermotoga thermarum were cloned and secretory expressed in Bacillu subtilis. Compared with Escherichia coli expression host, B. subtilis resulted in a 1.5 time increase of enzymatic activity for both recombinant enzymes. The optimal temperature and pH were 95 o C and 6.5 for Xyn, and 95 o C and 6.0 for XynB. Thermostability of both recombinant enzymes was observed between the temperature range of 75-85 o C. Molecular docking analysis through AutoDock showed the involvement of Glu525, Asn526, Trp774 and Arg784 in Xyn-ligand interaction, and Val237, Lys238, Val761 and Asn76 in XynB-ligand interaction, respectively.The recombinant Xyn and XynB exhibited synergistic hydrolysis of beechwood xylan and pretreated lignocellulose, where Xyn and XynB pre-hydrolysis achieved a better improvement of pretreated lignocellulose hydrolysis by commercial cellulase. The observed stability of the enzymes at high temperature and the synergistic effect on lignocellulosic substrates suggested possible application of these enzymes in the field of saccharification process.